2021
DOI: 10.1016/j.metop.2021.100125
|View full text |Cite
|
Sign up to set email alerts
|

Characterising Alzheimer's disease through integrative NMR- and LC-MS-based metabolomics

Abstract: Background Alzheimer's Disease (AD) is a complex and multifactorial disease and novel approaches are needed to illuminate the underlying pathology. Metabolites comprise the end-product of genes, transcripts, and protein regulations and might reflect disease pathogenesis. Blood is a common biofluid used in metabolomics; however, since extracellular vesicles (EVs) hold cell-specific biological material and can cross the blood-brain barrier, their utilization as biological material warrants further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…The decreased levels of BCAAs could affect glutamate synthesis, thereby impairing neurotransmission. Indeed, in line with lower BCAA levels in AD, a reduction in glutamate levels was reported in AD patients [ 266 ], together with decreased levels of glutamine [ 267 ]. Furthermore, since glutamate, as an excitatory neurotransmitter, binds to cell surface receptors such as α-amino-3-hydroxy-5-methyl-4-isoxazolopropionic acid (AMPA) receptors and N-methyl-D-aspartate (NMDA) receptors [ 268 ], and since reduction in NMDA receptor function relates to Ca 2+ dysregulation and reduced synaptic plasticity [ 269 ], it is conceivable that reduced BCAA levels contribute to dementia in AD [ 265 ] ( Figure 3 B).…”
Section: Metabolic Alterations In Ad and Pd Brainsmentioning
confidence: 85%
“…The decreased levels of BCAAs could affect glutamate synthesis, thereby impairing neurotransmission. Indeed, in line with lower BCAA levels in AD, a reduction in glutamate levels was reported in AD patients [ 266 ], together with decreased levels of glutamine [ 267 ]. Furthermore, since glutamate, as an excitatory neurotransmitter, binds to cell surface receptors such as α-amino-3-hydroxy-5-methyl-4-isoxazolopropionic acid (AMPA) receptors and N-methyl-D-aspartate (NMDA) receptors [ 268 ], and since reduction in NMDA receptor function relates to Ca 2+ dysregulation and reduced synaptic plasticity [ 269 ], it is conceivable that reduced BCAA levels contribute to dementia in AD [ 265 ] ( Figure 3 B).…”
Section: Metabolic Alterations In Ad and Pd Brainsmentioning
confidence: 85%
“… 40 4‐Pyridoxic acid is the product of vitamin B 6 , and it was increased in serum of MCI (mild cognitive impairment) and AD patients. 41 The main function of pantothenic acid, also called vitamin B 5 , is the synthesis of CoA and acyl carrier protein. A study had found that dietary intake of pantothenic acid was associated with cerebral amyloid burden in patients with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a cross‐sectional study in the older hospitalized patients revealed that patients with dementia and delirium had lower whole blood thiamine compared to those without 40 . 4‐Pyridoxic acid is the product of vitamin B 6 , and it was increased in serum of MCI (mild cognitive impairment) and AD patients 41 . The main function of pantothenic acid, also called vitamin B 5 , is the synthesis of CoA and acyl carrier protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, Nielsen et al found that inosine serum levels were reduced in AD patients [ 29 ]. Moreover, Alonso-Andrés et al demonstrated that the frontal cortex from the early stages of AD show apparently reduced levels of inosine, whereas the parietal cortex and temporal cortex show significantly higher levels of inosine, at least at certain stages of AD [ 30 ].…”
Section: Inosine In Admentioning
confidence: 99%